Microwave-Assisted in the Preparation of Nitrogen-DopedTiO2for the Photogradation of Organic Dyes: Effect of pH and Catalyst Dosage - M.S., Azami; Tan, K.H.; N., Jamaluddin; N.M., Izzudin; A.A., Azmi (Universiti Teknologi Malaysia, Johor, Malaysia, 2022)
The unmodified TiO2was modified using a microwave technique to produce a visible light active nitrogen (N) doped TiO2. The modified photocatalyst was prepared by mechanical mixing of unmodified TiO2with various amounts of urea and various irradiation power of micrcowave .It was observed that the N doped TiO2at 800 W of microwave power irradiation with urea content 3 g was defined as the optimum condition for a modified photocatalyst. N doped TiO2then was characterized using X-ray photoelectron spectroscopy (XPS), photoluminescence (PL) and UV-Vis diffuse reflectance spectra (UV-Vis/DRS) analyses. The XPS and PL proved that the successful nitrogen doped into the TiO2. XPS results presented with two peaks with binding energy 404.8 and 400.2 eV that indicates the formation of chemical interaction N with titania forming N doped TiO2.In addition, UV-Vis/DRS confirmed that the introduction of nitrogen into TiO2by decreasing the bandgap energy value from 3.02 eV to 2.9 eV. The photocatalytic activity study of N doped TiO2was carried out by irradiating 25 mL of 30, 10 and 5 mg L-1of anionic Reactive Red 4 (RR4), cationic Methyl Violet (MV) and cationic Janus Green dyes (JG) in the presence of fluorescent light and visible light (UV cut-off) with the rate of photodegradation was estimated from aliquot concentration spectrophotometrically. The irradiation of N doped TiO2was conducted using two parameters namely the effect of catalyts dosage and the effect of pH. It can be observed that 0.0012 g /mL of catalyst dosages that givesan optimum photocatalytic degradation for both anionic and cationic dyes. Effect of pH was conducted based on the optimum catalyst dosage and conclude that pH 4 and 8 were the optimum pH for anionic and cationic dyes respectively